Visual analysis of local content in English elementary textbook in Surakarta Indonesia: a focus on cultural local content - Honest, Ummi Kaltsum; Habiby, Wahdan Najib; Razali, Abu Bakar (UiTM Press, 2021)
English for elementary education policy in Indonesia states that English is categorized as a local content curriculum area. The local content curriculum is an educational program whose content and media (such as visuals) and delivery strategies are linked to the physical environment, social environment, and cultural environment and regional needs. Based on this government policy, some problems are raised. The objective of this research was to investigate the local content represented visually in the textbook (for example illustrations of cultural local contents that are represented in clothing, physical settings, and so on) that are stated and written in the fourth grade English textbook in Surakarta, Indonesia. This research is qualitative research using directed visual content analysis approach. The subject of focus in this research is the fourth grade English Textbook in the district of Surakarta Indonesia and the object is the visual local and cultural content illustrated in the textbook. The data analysis technique is based on Krippendorf analysis, to which the researchers unitized, sampled, recorded, reduced, inferred, and narrated the data from the analysis of the textbook. The validity of the data used in this study is the persistence of observation. The result of the study shows that local visual content found in the textbook which is tailored to the local and cultural characteristics of Surakarta is only found in Lesson 5 or only 10% from the overall content of the textbook. This means that 90% of the content of the textbook does not really cater visually to the local elements that are important for the identity and pride of Indonesian people in the city of Surakarta.